1996
DOI: 10.1177/1077727x960244007
|View full text |Cite
|
Sign up to set email alerts
|

Attachment‐to‐Home: A Contributing Factor to Models of Residential Mobility Intentions

Abstract: Traditional models of residential mobility use sociodemographic characteristics, housing characteristics, and residential satisfaction to explain the desire to move. This study compared the traditional mobility model with one that incorporated psychological attachment‐to‐home as an additional variable. Data were analyzed for 198 subjects who responded to a mail questionnaire and in‐depth telephone interview. Correlation analysis revealed that two attachment‐to‐home factors, as well as the respondent's age and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…One explanation for this link may be parents' concerns about their children's exposure to environmental and safety hazards, such as exposed wires and peeling paint, which have negative implications for child development (Evans 2006) and, consequently, may motivate families to find a new residence. The observed link between housing problems and residential mobility extends prior literature that has focused broadly on subjective dissatisfaction with a unit without quantifying specific issues with the unit (Earhart and Weber 1996). Also in line with hypotheses were the findings that families who moved into private market rentals experienced increased rates of mobility in comparison to families who moved into government housing assistance or homeownership.…”
Section: Strong Support For Housing and Neighborhood Contextssupporting
confidence: 64%
“…One explanation for this link may be parents' concerns about their children's exposure to environmental and safety hazards, such as exposed wires and peeling paint, which have negative implications for child development (Evans 2006) and, consequently, may motivate families to find a new residence. The observed link between housing problems and residential mobility extends prior literature that has focused broadly on subjective dissatisfaction with a unit without quantifying specific issues with the unit (Earhart and Weber 1996). Also in line with hypotheses were the findings that families who moved into private market rentals experienced increased rates of mobility in comparison to families who moved into government housing assistance or homeownership.…”
Section: Strong Support For Housing and Neighborhood Contextssupporting
confidence: 64%
“…His model was confirmed by Landale and Guest (1985) and showed that satisfaction is a strong predictor of into of moving and the intention of moving will influence the real move. Earhart and Weber (1996) and Oh (2003) argued that residential satisfaction influences the intention to move house by working together with other variable like feeling of home attachment and social bonding. Diaz-Serrano and Stoyanova (2010) used panel data collected from 12 countries to find that residential satisfaction also triggers real moves.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The aim of this paper therefore is to analyse how social-demographic variables and residential satisfaction jointly influence residential moving intentions allowing for identifying both the observed and unobserved heterogeneity between residents. Consistent with the mainstream residential mobility studies that concentrated 1 3 on the propensity to move (e.g., Earhart and Weber 1996;Kestens 2004;Liao 2004;Wu 2006;Kwon and Beamish 2013), our analysis will only consider the first stage of residential mobility, namely the mobility intention rather than real moves.…”
Section: Introductionmentioning
confidence: 99%
“…We examined the role of housing quality and place attachment in elderly citizens' psychological well-being. Housing quality is related to elderly community residents' sense of community and place attachment (Eshelman & Evans, 1998;Kweon, Sullivan, & Wiley, 1998), intentions to relocate (Earhart & Weber, 1996;O'Bryant & Murray, 1986;Rowles, 1983), and residential satisfaction (Christensen, Carp, Cranz, & Wiley, 1992;Lawton, 1980;Windley & Scheidt, 1983). Notably absent are assessments of mental health.…”
mentioning
confidence: 99%